Thirty‐Day Readmission Rates, Timing, Causes, and Costs after ST‐Segment–Elevation Myocardial Infarction in the United States: A National Readmission Database Analysis 2010–2014. Issue 18 (18th September 2018) - Kim, Luke K.; Yeo, Ilhwan; Cheung, Jim W.; Swaminathan, Rajesh V.; Wong, S. Chiu; Charitakis, Konstantinos; Adejumo, Oluwayemisi; Chae, John; Minutello, Robert M.; Bergman, Geoffrey; Singh, Harsimran; Feldman, Dmitriy N.
Abstract : Background: Readmission after ST‐segment–elevation myocardial infarction (STEMI) poses an enormous economic burden to the US healthcare system. Efforts to prevent readmissions should be based on understanding the timing and causes of these readmissions. This study aimed to investigate contemporary causes, timing, and cost of 30‐day readmissions after STEMI. Methods and Results: All STEMI hospitalizations were selected in the Nationwide Readmissions Database (NRD) from 2010 to 2014. The 30‐day readmission rate as well as the primary cause and cost of readmission were examined. Multivariate regression analysis was performed to identify the predictors of 30‐day readmission and increased cumulative cost. From 2010 to 2014, the 30‐day readmission rate after STEMI was 12.3%. Within 7 days of discharge, 43.9% were readmitted, and 67.3% were readmitted within 14 days. The annual rate of 30‐day readmission decreased by 19% from 2010 to 2014 ( P <0.001). Female sex, AIDS, anemia, chronic kidney disease, collagen vascular disease, diabetes mellitus, hypertension, pulmonary hypertension, congestive heart failure, atrial fibrillation, and increased length of stay were independent predictors of 30‐day readmission. A large proportion of patients (41.6%) were readmitted for noncardiac reasons. After multivariate adjustment, 30‐day readmission was associated with a 47.9% increase in cumulative cost ( P <0.001). Conclusions: Two thirds of patients were readmitted within the first 14 days after STEMI, and a large proportion of patients were readmitted for noncardiac reasons. Thirty‐day readmission was associated with an ≈50% increase in cumulative hospitalization costs. These findings highlight the importance of closer surveillance of both cardiac and general medical conditions in the first several weeks after STEMI discharge.